Tolerance of soybean genotypes to Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) - Victor, Vinicius S. [UNESP] (2022)
The neotropical brown stink bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) one of the most harmful and abundant insect pests of soybean crops—feeds from pod formation until the end of seed development, drastically reducing crop productivity. This study aimed to evaluate the response of soybean genotypes to different patterns of E. heros infestation, to characterize tolerance, and to investigate the physiological mechanisms involved. A tolerance test was performed in a greenhouse with the soybean genotypes ‘Conquista’, ‘IAC-100’, ‘TMG 7062 IPRO’, and ‘KS-4202’. Genotypes were physically isolated and various infestation patterns applied, using three stink bugs per plant. A simultaneous greenhouse experiment was performed to correlate the enzyme activity of superoxide dismutase, peroxidase, polyphenol oxidase, and catalase with genotype performance across the various levels of infestation. Finally, a field experiment was conducted with the same genotypes; plants were isolated and stink bugs applied at different phenological phases (7-day infestation beginning in R3, R5, and R7; and R3 until harvest). In the two greenhouse trials, the genotypes ‘IAC-100’ and ‘Conquista’ expressed tolerance to E. heros, suggesting an association with greater peroxidase activity. In the field, the ‘IAC-100’ genotype exhibited tolerance toward E. heros, showing high resistance when infested in the R5 and R7 phenological phases. The ‘TMG 7062’ genotype showed promising results infested with stink bugs in the R7 phase, under field conditions.The greenhouse and field results confirm the tolerance of ‘IAC-100’ to E. heros and indicate that oxidative enzymes may be related to the genotype’s physiological response when infested with this stink bug.